Financing an efficient adaptation programme to climate change: A contingent valuation method tested in Malaysia - Banna, Hasanul Banna; Rafia, Afroz; Masud, Muhammad Mehedi (EDP Sciences, 2016)
– This paper assesses farmers’ willingness to pay for an efficient adaptation programme to climate change for Malaysian agriculture. We used the contingent valuation method to determine the monetary assessment of farmers’ preferences for an adaptation programme. We distributed a structured questionnaire to farmers in Selangor, Malaysia. Based on the survey, 74% of respondents are willing to pay for the adaptation programme with several factors such as socio-economic and motivational factors exerting greater influences over their willingness to pay. However, a significant number of respondents are not willing to pay for the adaptation programme. The Malaysian government, along with social institutions, banks, NGOs, and media could come up with fruitful awareness programmes to motivate financing the programme. Financial institutions such as banks, insurances, leasing firms, etc. along with government and farmers could also donate a substantial portion for the adaptation programme as part of their corporate social responsibility (CSR)